Poverty - Sam Ray-Chaudhuri; Tom Waters; Xiaowei Xu (Institute for Fiscal Studies (IFS), 2023)
We investigate recent trends in poverty, and government policies aimed at alleviating it.
Keywords: 330; Consumption and prices; Employment and income; Poverty; inequality and social mobility; Poverty; Benefits; Consumer behaviour; COVID-19; Living standards; Universal credit; Working age benefits